'Do you know where I can buy ivory?': The illegal sale of worked ivory products in Hong Kong. Issue 2 (June 2018) - Wong, Rebecca WY
Set against the theoretical framework of situational crime prevention theory, this paper analyses the illegal sale of worked ivory products in Hong Kong, which is the city with the highest number of worked ivory products for retail sale in the world. Based on qualitative interviews and open sources, this paper shows that legalising the sale of products made from mammoth tusk and pre-1989 ivory, the low risk of detection, high rewards, justifications made by offenders, and unique situational conditions have collectively (and indirectly) created opportunities for traders to sell worked ivory items illegally in Hong Kong. This paper concludes by offering a discussion on why the illegal sale of ivory products cannot be prevented with situational crime prevention preventive strategies in the long run.